Shariah criminal mode of adjudication: distinctive features vis-à-vis modern systems - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (Zes Rokman Resources (2131022-P), 2019)
Modern discourse on adjudication has been made against the backdrop of the two dominant Western models of inquisitorial trial of the Civil Law and adversarial trial of Common Law. The fundamental feature of inquisitorial system is that it is that the judge who has the overarching role in adjudicating whilst the unique feature of adversarial system is that it is partisan-centric. As to which of the models Islamic mode of adjudication fits, opinion varies. Some comparative scholars assimilate it with adversarial model whilst others see it identical to inquisitorial model or having the features of both. Using qualitative method by undertaking a critical library reseach of some crucial works, this paper, however, argues that the Shariah mode of criminal trial though resembling some features of both, has certain unique features of its own. This is on account of its religiously colored conception of crime, notion of judicial function, methods and standard of proof and the role of attorney, which defies its equation with any of such models.